Implikasi Hukum Indonesia Menjadi Pihak Konvensi Beijing Tahun 2010 Dihubungkan dengan Keamanan Penerbangan Sipil di Indonesia - Rizka Nurhalilah (UNISBA Press, 2022)
abstract, Aviation is a unitary system consisting of the use of airspace, aircraft, airports, air transportation, flight navigation, safety and security, the environment, as well as other supporting facilities and public facilities. The role and function of air transportation is very important, especially from a political and economic point of view, which has led to the rapid development of the national aviation world. This development is not only in the number of airplanes but also in the number of national airlines. Aviation has a high risk for various parties such as aircraft companies, aircraft carriers, aviation service users and third parties on the surface of the earth. Risks that can occur include accidents or aircraft that cause serious damage to the equipment or facilities used and / or cause fatalities or serious injuries. In the world of aviation now compliance with high security standards is an important thing. The implementation of aviation security provides protection to aviation from unlawful actions through the integration of human resource utilization, facilities, and procedures. In anticipation of the unwanted happening, icao established a convention on aviation security as a refinement of the 1963 Tokyo Convention, the Montreal Convention of 1971, and the Montreal Protocol of 1988, the 2010 Beijing Convention. As an international rule on aviation safety